2018
DOI: 10.1007/s13280-018-1097-9
|View full text |Cite
|
Sign up to set email alerts
|

From waste to resource: A systems dynamics and stakeholder analysis of phosphorus recycling from municipal wastewater in Europe

Abstract: Recycling Phosphorus (P) from urban wastewater can secure part of domestic agricultural P supply and contribute to a circular P supply chain. In this paper, we use literature review, stakeholder interviews and analysis, and systems dynamics for the capital cities of Stockholm and Budapest as case studies. We find that political support is a prerequisite for developing the P recycling sector, and policy makers are the most influential stakeholders. P criticality is the main driver for political support. P exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Other similar studies have also reported on the benefits of using sewage sludge in agricultural production [5][6][7].…”
Section: Introductionmentioning
confidence: 86%
“…Other similar studies have also reported on the benefits of using sewage sludge in agricultural production [5][6][7].…”
Section: Introductionmentioning
confidence: 86%
“…In order to identify operation methods to solve the complex problems of eutrophication process management, the following key aspects should be distinguished: Advanced wastewater treatment technologies can theoretically provide exceptionally high efficiencies for pollution reduction; however, treatment costs increase exponentially and the community is often unable to bear such financial burdens (Jiang et al 2004 ; Nedelciu et al 2019 ). With the increasing complexity of technological systems and the intensification of the applied processes, environmental pressure caused mostly by increased energy consumption and greenhouse gas emissions increases significantly (Henriques and Catarino 2017 ; Castellet-Viciano et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Advanced wastewater treatment technologies can theoretically provide exceptionally high efficiencies for pollution reduction; however, treatment costs increase exponentially and the community is often unable to bear such financial burdens (Jiang et al 2004 ; Nedelciu et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Circular Economy Package aims to boost large-scale production of fertilizer from organic waste, while in the meantime, it is expected to impose lower EU-wide limits on heavy metal concentration in fertilizers [18,19]. Nedelciu et al [20] underline how at the municipal level, the recycling of phosphorus from wastewater can contribute to the achievement of the EU Circular Economy Package objectives, reduce the import dependency of this scarce resource, and tackle the problem of eutrophication. The support of policies such as those envisaged in the Farm to Fork and Biodiversity 2030 Strategies of the EU, which aims to halve chemical pesticides use by 2030, would benefit organic production, and local consumption would benefit from significant gains in terms of work and health for the urban area.…”
Section: Introductionmentioning
confidence: 99%